Analysis and Review of “The Story of the Beloved Ones’ Secrets” Researching the Historical Living and Experiences of Molana in Masnavi - Mostafa Gorji (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the important and earnest investigations in the field of “study of Molavi”, through the recent decade, is a book named “The Story of the Beloved Ones’ Secret” that emphasizes on Masnavi researching. The secondary title of this book is “Researching the Historical Living and Experiences of Molana in Masnavi”. The book is written by Qodrat-Allah Taheri and published by Elmi Publication (1392 (or 2013)). Emphasizing on three presumptions, this is probably the only book that independently attempts to investigate and analyze the lived experience of Molavi in the most important mystical writing of him. The book considers the story of Masnavi, especially the most leading ones, to be the alternative reflections of Molavi’s states and actions in his real life. To what extent our claim and research objectives are proven and fulfilled regarding the text based evidenced and statistics with an absolute emphasis on Masnavi is an important matter which we reviewed. This article, first, investigated the advantages and unique characteristics of the book in terms of methodology and insight, and second, it focused on the most important challenging features and defects.